Leprosy patients: neurotrophic factors and axonal markers in skin lesions - Letícia Baccaro Michellin; Jaison Antonio Barreto; Lúcia Helena Soares Camargo Marciano; Flavio Alves Lara; Maria Esther Salles Nogueira; Vânia Nieto Brito de Souza; Maria Renata Sales Nogueira Costa (Arquivos de Neuro-Psiquiatria)
Neurotrophins are growth factors with crucial roles in neural pathophysiology. These mediators functionally modulate nociceptive fibers, and changes in neurotrophins expression have been correlated with early loss of nociception in leprosy. This study investigated the expression of NGF, BDNF, and NT3 in dermal nerves of leprosy patients. Characterization of Remak bundles was achieved by p75NTR, and axonal markers NF-L and PGP 9.5 immunostaining. Clinical parameters of neural impairment have been evaluated by Semmes-Wenstein monofilaments. Our findings demonstrated decrease of NGF in borderline leprosy, when compared to control specimens. Similar results were observed in PGP 9.5 expression (borderline: p<0.001 and lepromatous: p<0.05) and NF-L (lepromatous: p<0.05), suggesting advanced Remak bundles degeneration in multibacillary leprosy. It has also been observed positive correlation between p75NTR and PGP 9.5, indicating association between Schwann cells and axons in Remak bundles. Present data indicate that neurotrophins imbalance may participate in the establishment of peripheral nerve damage.